In vitro comparison of low-power diode pumping solid-state laser radiation at 589 and 650 nm on red blood cells suspension viscosity, stability, and deformability - Munawar Luie Esmaiel; Mustafa Salih. Al Musawi; Bassam Talib Al-Gailani (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the effect of diode-pumped solid-state laser irradiation with yellow 589nm and red 650nm wavelengths on rheological parameters in vitro. Method: The comparative study was conducted between November 2021 and April 2022 at the at the Postgraduate Medical Physics Laboratory, Mustansiriyah University, Baghdad, Iraq, and comprised blood samples from healthy adult volunteers. The samples were divided into 4 aliquots. The first was preserved as a control sample, while the other 3 were exposed to a diode-pumped solid-state laser, delivering the beam for 589nm and 650nm wavelengths at radiation dose 15, 22.5, 33.5J/cm2 for 20, 30 and 45 minutes, and with each laser having a 50mW output power and a 4 mm2 spot diameter. Data was analysed using SPSS (version 24) Results: There were 6 subjects aged 18-60 years. There was no significant difference in the viscosity values between laser wavelengths (p>0.05). Compared to the laser wavelength of 650nm, irradiation with a 589nm wavelength at the same dose resulted in a significant reduction (p<0.009) in deformability. The rigidity index of red blood cell suspension was reduced the most at a radiation dose of 22.5J/cm2 for both lasers compared to the control samples. No significant variations were found in suspended erythrocyte viscosity (p>0.05). Conclusion: The wavelength with 589nm lasers showed more effective influence than its 650nm counterpart in improving the rheological parameters of blood viscosity and erythrocytes deformability. Key Word: Lasers, Viscosity, Erythrocytes, Radiation,